BANGUNAN PENJARA DAN PELAKSANAAN PENGHUKUMAN - Praditya Mer Hananto (SISI LAIN REALITA, 2016)
All of design in architecture building have some particular composition, compilation and presentation which is exclusively affecting the user inside. Each design have its own world of scope or characteristic which is symbolzed within definition of social relationship. The researcher interested in prison building, a place to implementing a punishment. According to Peter Severin, there is 3 function of prison architecture : confining criminals to protect society, punishing those individuals, and correcting their behavior make them return to society. But the last function is the hardest part and the right design continue to be sought. By studying various literature about prisons architecture design and how punishment implimented, the researcher analyzing pros and cons of each prison design in carrying out the punishment. This research is conducted that each prisons design have its own abilitys, wherein by covering weakness of previously prisons design will resulting in new prison design which is better for implementing punishment. Matter like prisons layout, cels shape, technology, up to materials used was important instrumental to achieving more appropriate design in the effort to reintegarting the convict to society.